Kinetics of Hydrolysis of Mono-p-toluidine Phosphate Catalyzed by Hydrochloric Acid - Awadhiya, Pragya; Bhoite, S.A. (Asian Journal of Chemistry, 2010)
Kinetic study of the hydrolysis of mono-p-toluidine phosphate has been carried out in 0.1 to 7.0 M HCl at 50 ± 0.5 ºC. The rate of hydrolysis increases with increase in acid molarity up to 4 M HCl and after that it decreases. The lowering of rates after 4 M HCl has been attributed to the effect of water activity. Rate data at constant ionic strength is used to identify reactive species and to determine theoretical rates. Hydrolysis of monoester via conjugate acid species has been assigned the bimolecularity of the reaction on the basis of Arrhenius parameters, Zucker- Hammett hypothesis and Bunnett & Bunnett-Oleson's parameters. Solvent effect has been found to indicate the formation of a transition state in which charge dispersion occurs. Kinetic rate data and isokinetic relationship have been used to propose the probable bond fission.